High-resolution transmission electron microscopy study of crystallography and morphology of TiC precipitates in argon-irradiated 18Cr10NiTi steel - Kalchenko, A.S.; Karpov, S.A.; Tolstolutskaya, G.D. (Вопросы атомной науки и техники, 2021)
This work encompasses identification of the crystal structure and analysis of the TiC precipitates in 18Cr-10Ni-Ti austenitic stainless steel under Ar-ions irradiation. High resolution transmission electron microscopy (HRTEM) and energy dispersive spectroscopy (EDS) are used. Orientation relationship of TiC particles in surrounding matrix are indicated by HRTEM and diffraction patterns. The size of the precipitates is found to be critical: the coherency of TiC is kept at the interfaces when the precipitate is in the stage of nucleation, whereas the growth of precipitate up to 10 nm can lead to the loss of coherency in the austenitic steel. The findings suggest that the incoherent precipitate-matrix interface is an important point defect sink and contributes to inert gas bubble formation at elevated irradiation temperatures. Проведено ідентифікацію кристалічної структури та аналіз виділень TiC в аустенітній нержавіючій сталі Х18Н10Т під опроміненням іонами Ar. Використовуються трансмісійна електронна мікроскопія з високою роздільною здатністю (ТЕМВРЗ) та енергодисперсійна спектроскопія (ЕДС). Орієнтаційна залежність часток TiC у навколишній матриці вказується ТЕМВРЗ та дифракційними картинами. Встановлено, що розмір виділень є критичним: когерентність TiC зберігається на межах розділу, коли виділення знаходиться на стадії зародження, тоді як зростання виділення до 10 нм може призвести до втрати когерентності в аустенітній сталі. Висновки свідчать про те, що некогерентна межа розділу виділенняматриця є важливим стоком точкових дефектів і сприяє утворенню бульбашок інертного газу при підвищених температурах опромінення. Проведены идентификация кристаллической структуры и анализ выделений TiC в аустенитной нержавеющей стали Х18Н10Т при облучении ионами Ar. Используются просвечивающая электронная микроскопия высокого разрешения (ПЭМВР) и энергодисперсионная спектроскопия (ЭДС). Ориентационные отношения частиц TiC в окружающей матрице показаны с помощью ПЭМВР и дифрактограмм. Установлено, что размер выделений критичен: когерентность TiC сохраняется на границах раздела, когда выделение находится на стадии зарождения, тогда как рост выделения до 10 нм может привести к потере когерентности в аустенитной стали. Полученные данные свидетельствуют о том, что некогерентная граница раздела выделение-матрица является важным стоком точечных дефектов и способствует образованию пузырьков инертного газа при повышенных температурах облучения.